Influence of heating temperature, pH and ions on recrystallization inhibition activity of κ-carrageenan in sucrose solution. (February 2017) - Leiter, Andreas; Ludwig, Alexander; Gaukel, Volker
Abstract: The objective of this study was to investigate the influence of heating temperature and pH on ice recrystallization inhibition (IRI) activity of κ-carrageenan. Results showed that temperature treatment up to 30 min at 80 °C has no influence on IRI activity. Recrystallization experiments at different pH adjusted by hydrochloric acid and sodium hydroxide demonstrated that the presence of sodium cations and not pH is responsible for a decreasing IRI activity with increasing sodium concentration. In addition, it was shown that the IRI activity of κ-carrageenan depends on the type of ion. We assume that these effects are related to gelation of κ-carrageenan which reduce the IRI activity. Furthermore, IRI activity in pH 1 solution was strongly improved. Our previous assumption that IRI activity originates from an interaction with the ice crystal surface is supported by our findings that ice crystals are more angular in solutions where κ-carrageenan exhibits IRI activity. Highlights: Heating times up to 30 min at 80 °C have no influence on recrystallization inhibition. Presence of ions influence ice recrystallization inhibition activity of κ-carrageenan. Type of ions influence ice recrystallization inhibition activity of κ-carrageenan. Recrystallization inhibition activity decreases with increasing sodium concentration. Ice crystal shape depends on ice recrystallization inhibition activity.